Monkeys On A Fast - Kaushik Viswanath (India Karadi Tales, 2015)
Chakrapani, the monkey chieftain decides that the only way for his tribe to lose weight is by going on a fast. But can hungry monkeys stop eating? Even for a day? Wacky illustrations by Shilpa Ranade add mischief to this hilarious story adapted by Kaushik Viswanath from a Buddhist tale.
Keywords: Read Aloud -- Read Aloud